Knowledge Sharing Behavior among Academic Staff of Universiti Utara Malaysia - Nur Syazwani, Mohd Nawi (2009)

(untitled)
This study was implementing Theory of Planned Behavior (TPB) to study knowledge sharing behavior among academic staffs of Universiti Utara Malaysia (UUM). The main objective of this study was threefold. First, the study was to examine the relationship between attitude, subjective norm and perceived behavioral control with knowledge sharing behavior. Second, it was to determine whether intention plays a mediating role in this relationship. Third, was to find out the relationship between intention and knowledge sharing behavior. A total of 250 questionnaires were distributed to academic staffs from three (3) academic colleges which are College of Business (COB), College of Arts and Sciences (CAS) and College of Law, Government and International Studies (COLGIS). However, only 98 were returned and usable for analysis. Hierarchical regression analysis was performed to tests the hypotheses of the study. The results indicated that of the three (3) components of TPB, only attitude and perceived behavioral control were positively and significantly related to knowledge sharing behavior. However, the regression analysis showed that only attitude was significant predictors of intention. It was found that, intention was not a mediator in the relationship between perceived behavioral control and knowledge sharing behavior. The findings were discussed and recommendations for the future research were also addressed.